The effect of oral curcumin capsules on symptoms of premenstrual syndrome and dysmenorrhea: a randomized controlled trial - Fatemeh Shabani; Sepideh Mashayekh-Amiri; Fatemeh Teihoomaneshfard; Mahsa Hesami; Elnaz Shaseb; Mojgan Mirghafourvand (Journal of Pharmaceutical Health Care and Sciences)
Abstract Background Given the high prevalence of menstrual disorders such as premenstrual syndrome (PMS) and dysmenorrhea among students and the anti-inflammatory and antioxidant properties of curcumin, we decided to conduct a study to determine the effects of curcumin on PMS and dysmenorrhea among medical students in Tabriz-Iran. Methods This double-blind randomized controlled trial was conducted on 62 students from Tabriz University of Medical Sciences in Iran during the 2023–2024 academic year. The participants were randomly assigned to the intervention (n = 31) and control (n = 31) groups. They were given curcumin and placebo capsules with the same dose of 500 mg once daily for 10 days during each of the two menstrual cycles (7 days before to 3 days after the estimated onset of menstruation). Data collection involved a sociodemographic characteristics questionnaire, the Premenstrual Symptoms Screening Tool (PSST), the Visual Analogue Scale (VAS), and a checklist to evaluate potential side effects. Independent t test and ANCOVA were employed to compare the results between the two groups. Results There was no significant difference between the study groups regarding sociodemographic characteristics and baseline values before the intervention. Based on the ANCOVA test and by adjusting the baseline values, the curcumin group showed a significant reduction in average score of PSST in 2nd menstrual cycle (MD: -5.2; 95% CI: -9.6 to -0.9; P = 0.018) and average score of VAS in 2nd menstrual cycle (MD: -0.8; 95% CI: -1.4 to -0.1; P = 0.012) and 3rd menstrual cycle (MD: -0.8; 95% CI: -1.5 to -0.08; P = 0.029) compared to the placebo group. None of the study groups reported adverse effects. There were no dropouts and all participants completed the treatment period successfully. Conclusion This study highlights the increasing evidence that curcumin is an effective natural treatment for PMS and dysmenorrhea. Further research into dose optimization, combination therapies, and long-term effects will strengthen its position in clinical practice. Trial registration Iranian Registry of Clinical Trials (IRCT) IRCT20120718010324N71. Date of first registration 18/09/2022. Date of first sampling 20/09/2022. URL https://irct.behdasht.gov.ir/trial/65582 .